Maternal Deaths: Do Women still have the Right to Life? A Case Study in Nias Island - Zaluchu, Fotarisman; Wieringa, Saskia; Kok, Bregje de (Jurnal Perempuan, 2017)
This paper attempts to analyze maternal mortality in Nias Island, North Sumatra, where MMR is relatively higher than in other areas in Indonesia. This paper tries to examine the basic right highlighted in ICPD 1994 PoA. In addition, Corrêa and Petchesky propose that the fulfillment of women’s reproductive health rights must meet four principal elements, those are, bodily integrity, personhood, equality, and diversity. In line with the perspective suggested by Correa and Petchesky, this paper demonstrates the “omission, neglect, or discrimination” of women’s right for reproductive health. Social actors who play important roles in women’s reproductive health assessed in this paper are husbands, mother’s-in-law, TBAs, midwifes, and the government. This research concludes that maternal mortality in Nias and in Indonesia is a persistent problem since the social actors who are supposed to be responsible to prevent maternal mortality fail to do their job well. Instead, they tend to intentionally negate women’s right of reproductive health.